Peran Pembelajaran STEAM Terhadap Perkembangan Kognitif Anak Usia Dini - Gladys Suryaniputri Hinadonu; Gracia Fortuna; Grace Bernadeth Sipa; Nonce Herlina Mailan; Sonia Melani Banik; Agnes Tefa; Fredericksen Victoranto Amseke (FKIP UNSULTRA, 2026)
Cognitive development is an important aspect in early childhood education because it is the foundation for thinking skills, problem solving, and understanding the surrounding environment. One learning approach that is considered effective in stimulating children's cognitive development is STEAM (Science, Technology, Engineering, Art, and Mathematics) learning. This study aims to determine the effect of STEAM learning on the cognitive development of early childhood. The method in this study is quantitative. The sampling technique used purposive sampling, namely children aged 4-6 years (grade B). The respondents of this study were 20 children aged 4-6 years at Kharisma Bello Kindergarten, Kupang City. The data collection technique used a questionnaire with instruments in the form of a STEAM learning scale and cognitive development. The STEAM learning scale was developed by Judith A. Ramaley (2001) called STEAM. The cognitive development scale was developed by Piaget (1996). The data analysis technique was simple linear regression. The findings found that STEAM learning had a positive and significant effect on the cognitive development of children aged 4-6 years by 31.1%, which means that better STEAM learning can improve the cognitive development of early childhood. It is hoped that children will engage in various forms of STEAM learning, both at home and at school, so they can learn about science, technology, engineering, art, and mathematics, thereby fostering the development of their cognitive abilities